Feasibility Analysis of Vanname Shrimp Ponds in Various Cultivation Technology Systems (Case Study in Manakku Village, Labakkang District, Pangkep Regency) - Amri, Muhammad Irwandhi; Haris, Abdul; ., Jumiati (Torani Journal of Fisheries and Marine Science, 2022)
Vanname shrimp is a fishery commodity that is currently popular with many people because vanname shrimp is more free and resistant to disease and is a promising business prospect for cultivators. Shrimp cultivation business in educational ponds at the University of Muhammadiyah Makassar located in Manakku Village, Labakkang District, Pangkep Regency is a business with vanname shrimp commodities. This study aims to determine the amount of costs and income, business studies on various vanname shrimp culture technologies carried out by 3 vanname shrimp farmers. This is done to assess whether the cultivation business is feasible or not feasible to be developed. Based on the business studies carried out, it can be seen that the vanname shrimp cultivation business in the education pond is profitable. The research results obtained are; 1) The investment cost for each farmer is Rp. 19,000,000,-. The total cost of vanname shrimp farming per farmer is Rp. 71.818.750, -, Rp. 140,685,000, -, and Rp. 207,712,500,-. The total cost of vanname shrimp farming is the sum of fixed costs and variable costs. The total income of vanname shrimp farming business earned by each farmer is Rp. 44,871,250,-, Rp. 75,960,000, -, and Rp. 67.287.5000,-. 2) The study of shrimp farming resulted in R/C ratio per farmer of 1.62, 1.54 and 1.32, the value of B/C Ratio of 0.62, 0.54 and 0.32, Break Event Point (BEP ) divided into 2, namely BEP Volume and BEP price. The value of BEP Production/volume per farmer is 1025.98 kg, 2164.38 kg, and 41542.50 kg, while the price BEP is Rp. 43,083, Rp. 42,210 and Rp. 41,543.